Clinical outcomes in patients with ST-segment elevation myocardial infarction treated with everolimus-eluting stents versus bare-metal stents (EXAMINATION): 5-year results of a randomised trial. Issue 10016 (23rd January 2016) - Sabaté, Manel; Brugaletta, Salvatore; Cequier, Angel; Iñiguez, Andrés; Serra, Antonio; Jiménez-Quevedo, Pilar; Mainar, Vicente; Campo, Gianluca; Tespili, Maurizio; den Heijer, Peter; Bethencourt, Armando; Vazquez, Nicolás; et al.
Summary: Background: Data for the safety and efficacy of new-generation drug-eluting stents at long-term follow-up, and specifically in patients with ST-segment elevation myocardial infarction, are scarce. In the EXAMINATION trial, we compared everolimus-eluting stents (EES) with bare-metal stents (BMS) in an all-comer population with ST-segment elevation myocardial infarction. In this study, we assessed the 5-year outcomes of the population in the EXAMINATION trial. Methods: In the multicentre EXAMINATION trial, done in Italy, Spain, and the Netherlands, patients with ST-segment elevation myocardial infarction were randomly assigned in a 1:1 ratio to receive EES or BMS. The random allocation schedule was computer-generated and central randomisation (by telephone) was used to allocate patients in blocks of four or six, stratified by centre. Patients were masked to treatment assignment. At 5 years, we assessed the combined patient-oriented outcome of all-cause death, any myocardial infarction, or any revascularisation. Analysis was by intention to treat. This trial is registered withClinicalTrials.gov, numberNCT00828087 . Findings: 1498 patients were randomly assigned to receive either EES (n=751) or BMS (n=747). At 5 years, complete clinical follow-up data were obtained for 731 patients treated with EES and 727 treated with BMS (97% of both groups). The patient-oriented endpoint occurred in 159 (21%) patients in the EES group versus 192 (26%) in the BMS group (hazard ratio 0·80, 95% CI 0·65–0·98; p=0·033). This difference was mainly driven by a reduced rate of all-cause mortality (65 [9%] vs 88 [12%]; 0·72, 0·52–0·10; p=0·047). Interpretation: Our findings should be taken as a point of reference for the assessment of new bioresorbable polymer-based metallic stents or bioresorbable scaffolds in patients with ST-segment elevation myocardial infarction. Funding: Spanish Heart Foundation.